Model of Digital Education for Student with Disabilities in an Affiliation of Special Education Bureau in Thai Supply Chain - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The objective of paper was to study and to evaluate model of digital education for student with disabilities in an affiliation of special education bureau in Thai supply chain. Samples group in the paper study consisted of ten purposively selected experts consisted of five experts on supply chain, two experts on digital, three expert on s p e c i a l education. Data were analysed by arithmetic mean and standard deviation. The paper findings pattern seven elements namely main components, Suppliers , Manufacture , customers, consumers, satisfaction, feedback . The assessment model of digital education for student with disabilities in an affiliation of special education bureau in Thai supply chain using Black- Box technique and The results from experts agreement model of digital education for student with disabilities in an affiliation of special education bureau in Thai supply chain was a high level The rating mean of 3.67 and standard deviation of 0.64. that mean the model to may be applied in support the tasks.